Analysis of Contemporary College Students' Attitudes towards "Double Eleven" from the Perspective of Marketing - Rong, Ziting; Pan, Jia (International Journal of Global Economics and Management, 2023)
Double Eleven is a popular Shopping festival in China. College students have become one of the main forces in online shopping on "Double Eleven." This paper mainly explores the attitudes of college students towards "Double Eleven" and its changing trends from the perspective of marketing, using a questionnaire survey. The results indicate that the current college student group has begun to shift from "blind shopping" to rational shopping on "Double Eleven." However, impulsive and herd behaviour, as well as certain consumption risks, still exist in their online shopping behaviour. Studying college students' attitudes towards "Double Eleven" is not only conducive to guiding them to establish correct shopping concepts but also provides a reference basis for e-commerce to innovate marketing methods.